Numerical simulation of three-dimensional laminar multiple impinging square jets - Aldabbagh, LBY; Sezai, I (Elsevier Science Inc, 2002)
The flow and heat transfer characteristics of impinging laminar multiple square jets have been investigated numerically through the solution of the three-dimensional Navier-Stokes and energy equations in steady state. The simulations have been carried out for jet-to-jet spacings of 4D, 5D and 6D and for nozzle exit to plate distances between 0.25D and 9D, where D is the jet width. The calculated results show that the flow structure of multiple square jets impinging on a heated plate is strongly affected by the jet-to-plate distance. On the other hand, the magnitude of the local maximum Nusselt number at the stagnation point is not affected by jet-to-jet spacing. Moreover, for very small jet-to-plate distances (L(z)approximate to0.25D), no upwash-fountain flow can form at the collision point, where the jets are merely diverted in the transverse direction. For such rather low nozzle-to-plate distances the wall jet fills the whole gap between the plates where no vortex motion forms around the jets. (C) 2002 Elsevier Science Inc. All rights reserved.
Keywords: three-dimensional laminar multiple impinging square jets